Aktivitas Antimikroba Kefir Susu Sapi yang Diinkubasi pada Tempurung Kelapa Hijau Muda terhadap Staphylococcus aureus dan Escherichia coli - Muna Yuniarti; Sri Anggreni Lindawati; I Gusti Agung Arta Putra (Jurnal Ilmiah Teknologi Pertanian Agrotechno, 2021)
This study aims to determine the antimicrobial activity of cow's milk kefir incubated a light green coconut shell against Staphylococcus aureus and Escherichia coli. This study used a completely randomized design (CRD) with three treatments and five replications. The three treatments were: incubated cow's milk kefir in a jar as a control (P0), incubated cow's milk kefir in a light green coconut shell without meat (P1), cow's milk kefir incubated in a light green coconut shell with meat (P2). The variables observed were kefir antimicrobial activity against Staphylococcus aureus ATCC 3351, Escherichia coli ATCC 8739 and the pH value and total lactic acid bacteria. The results showed that the antimicrobial activity of kefir against Staphylococcus aureus ATCC 3351 and Escherichia coli ATCC 8739 in all treatments (P2, P1 and P0) showed no significant difference (P> 0.05) with clear zone diameters of 10.50 - 11.30 mm and 9.70 mm. - 11.03 mm, followed by the pH value in treatment P2 (3.95), P1 (4.11), and P0 (4.38) were statistically significantly different (P <0.05), and the total lactic acid bacteria at P2, P1 and P0, respectively 14.3 x 106 CFU/g; 13.5 x 106 CFU / g and 8.1 x 106 CFU / g were not significantly different (P> 0.05). The conclusion of this study is that incubated cow's milk kefir on light green coconut shells has antimicrobial activity against Staphylococcus aureus ATCC 3351 and Escherichia coli ATCC 8739.